2011
DOI: 10.1124/jpet.111.180737
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of p38 Mitogen-Activated Protein Kinase Inhibition with a Corticosteroid in Alveolar Macrophages from Patients with Chronic Obstructive Pulmonary Disease

Abstract: Corticosteroids partially suppress cytokine production by chronic obstructive pulmonary disease (COPD) alveolar macrophages. p38 mitogen-activated protein kinase (MAPK) inhibitors are a novel class of anti-inflammatory drug. We have studied the effects of combined treatment with a corticosteroid and a p38 MAPK inhibitor on cytokine production by COPD alveolar macrophages, with the aim of investigating dose-sparing and efficacy-enhancing effects. Alveolar macrophages from 10 patients with COPD, six smokers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 34 publications
10
70
1
1
Order By: Relevance
“…These experiments further confirmed that CXCR2 antagonism alone through SB656933 was less effective than dual antagonism of CXCR1 and CXCR2 using Sch527123 in this chemotaxis model. There was no difference in the effect of dexamethasone between patients with COPD and smokers in the current study, in agreement with our previous work (Jones et al, 1996;Armstrong et al, 2011;Southworth et al, 2012). Alveolar macrophage numbers are increased in patients with COPD compared with controls (Di Stefano et al, 1998;Barnes, 2004;Hogg et al, 2004), contributing to an increased burden of inflammatory mediators found in the lungs of patients with COPD such as CXCL8 (Yamamoto et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These experiments further confirmed that CXCR2 antagonism alone through SB656933 was less effective than dual antagonism of CXCR1 and CXCR2 using Sch527123 in this chemotaxis model. There was no difference in the effect of dexamethasone between patients with COPD and smokers in the current study, in agreement with our previous work (Jones et al, 1996;Armstrong et al, 2011;Southworth et al, 2012). Alveolar macrophage numbers are increased in patients with COPD compared with controls (Di Stefano et al, 1998;Barnes, 2004;Hogg et al, 2004), contributing to an increased burden of inflammatory mediators found in the lungs of patients with COPD such as CXCL8 (Yamamoto et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…Alveolar macrophage numbers are increased in patients with COPD compared with controls (Di Stefano et al, 1998;Barnes, 2004;Hogg et al, 2004), contributing to an increased burden of inflammatory mediators found in the lungs of patients with COPD such as CXCL8 (Yamamoto et al, 1997). The production of CXCL8 by macrophages is only partially suppressed by corticosteroids in patients with both COPD and controls (Jones et al, 1996;Armstrong et al, 2011), but this limited effect is more clinically relevant in patients with COPD as the levels of CXCL8 after corticosteroid treatment still cause neutrophil chemotaxis. CXCL8 release is inhibited by 68% by dexamethasone (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blots were run as described previously [20]. All primary antibodies were raised in rabbit: phospho-p38 MAPK (Th180/Tyr182) antibody (Cell Signalling, Hitchin, UK), phospho-p44/42 MAPK (ERK1/2) (Thr202/Tyr204) antibody (Cell Signalling), phospho-NF-κB p65 (Ser536) antibody (Cell Signalling) and β-actin antibody (Abcam) as loading control.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Corticosteroids only partially suppress cytokine production from COPD alveolar macrophages [18][19][20]. There is an urgent need for more effective antiinflammatory therapies for COPD that target macrophage function.…”
Section: Introductionmentioning
confidence: 99%